Management of the Poxim-Açu River: a Swat model for evaluating irrigation scenarios (Research, Society and Development, 2022)
The present work has as main objective to apply the SWAT model to the Poxim-Açu River watershed, carrying out an assessment of its water production, having as object of study the filling of the Sindicalista Jaime Umbelino de Souza dam (São Cristóvão/SE). The problem is justified by the growing relevance of knowledge of the hydrological complex for the management of natural resources, due to its aid in decision making. Recording data measurements will later be used in 4 irrigation scenarios in two areas of the basin. It seeks to test the applicability of the model in studies of hydrological balance in small basins and the effects of natural interactions and human action, with the use of irrigation, on the flows and volumes produced. Through this study it can be concluded that: the SWAT model is applicable in the realization of simulations of water production and in the studies of the hydrological balance in the hydrographic basin of the Poxim-açú river; the development of a validating procedure, from the accumulation of water in the filling of a reservoir, allowed the evaluation of irrigation use scenarios; carrying out irrigation practices using water directly from the rivers would cause significant reductions in the volumes produced and could affect the filling of the Sindicalista Jaime Umbelino de Souza dam in São Cristovão-SE and the use of water for irrigation, coming from the shallow aquifer , can lead to reductions in the flows of the Poxim-açú River.